Pengaruh Kualitas Layanan, Orientasi Layanan, dan Strategi Harga terhadap Kepuasan dan Loyalitas Pelanggan (Studi Terhadap Pelanggan Jasa Transportasi Kereta Api Eksekutif) - Retnowati, Nova (Jurnal Aplikasi Manajemen, 2009)
This research is intended to prove and to analyze the influences of service quality, service orientation, and price strategy upon the satisfaction and customer loyalty of executive trains. Data of the research were collected by using questionnaire. Population in this research was the customer of executive trains. The data were analyzed by means of Structural Equation Modeling (SEM) technique assisted by the computer program of Partial Least Square (PLS). The findings obtained from this research are as follow: (1) service quality has influence upon the customer satisfaction of executive trains; (2) service orientation has not influence upon the customer satisfaction of executive trains; (3) price strategy has influence upon the customer satisfaction of executive trains; (4) service quality has not influence upon the customer loyalty of executive trains; (5) service orientation has not influence upon the customer loyalty of executive trains; (6) price strategy has not influence upon the customer loyalty of executive trains; and also (7) customer satisfaction has influence upon the customer loyalty of executive trains.